Stator faults detection on induction motors using harmonic sequence current components analysis - Mazzoletti, Manuel Armando; Donolo, Pablo Daniel; Pezzani, Carlos Martín; Oliveira, Mario Orlando; Bossio, Guillermo Rubén; Angelo, Cristian Hernán De (Institute of Electrical and Electronics Engineers, 2021)
Fil: Mazzoletti, Manuel Armando. Universidad Nacional de Misiones; Argentina.